Van Helsing the London assignment - Ducsay, Bob.; Sommers, Stephen; Jackman, Hugh.; Beckinsale, Kate.; Roxburgh, Richard; Wenham, David, 1965-; Kemp, Will, 1977-; Hensley, Shuler; Dariau, Allen; Silvestri, Alan.; Pescucci, Gabriella; Cameron, Allan; et al. (Universal City, CA : Distributed by Universal Home Video, 2004)
Deep in the heart of London, the sinister creature, Mr. Hyde, terrorizes the late-night streets in a haunting crime spree. With the city in a panic, the Knights of the Holy Order send Van Helsing into London with the mission of tracking down and capturing the evil Mr. Hyde.
Title from container.
Special features: cast and crew interviews; in-depth look at "Van Helsing"; the ground breaking special effects.
Director of photography, Allen Dariau ; editor, Bob Ducsay ; music, Alan Silvestri ; costume designer, Gabriella Pescucci ; production designer, Allan Cameron ; visual effects supervisor, Mark Freund.
Voices: Hugh Jackman, Kate Beckinsale, Richard Roxburgh, David Wenham, Will Kemp, Shuler Hensley.
MPAA rating: Not rated.
DVD, region 1, widescreen presentation; Dolby Digital.
Keywords: Crime -- England -- London -- Drama; Criminal behavior -- Drama; Animated films; Action and adventure films